2011
DOI: 10.4077/cjp.2011.amm045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hot and Cold Foods on Signals of Heart Rate Variability and Nail Fold Microcirculation of Healthy Young Humans: A Pilot Study

Abstract: Down-regulation of microglial activation represents a practical strategy for combating diverse brain disorders such as stroke and neurodegenerative diseases. In the present study, we showed evidence that isopropyl 3-(3, 4-dihydroxyphenyl)-2-hydroxypropanoate (IDHP), a new bioactive metabolite of Danshen (Salvia miltiorrhiza Bunge), exerted an anti-inflammatory effect in lipopolysaccharide (LPS)- induced microglia. Our data showed that IDHP significantly reduced the production of nitric oxide (NO), tumor necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In general, it is well accepted that NF-κB activation is one of the principal pathways that induce expression of inflammatory molecules in microglia (Wang et al, 2012, Park et al, 2013). Interestingly, increasing evidence suggests the NF-κB pathway as a possible mechanism in which inhibition of autophagy results in attenuation of inflammatory responses (Jiang et al, 2012, Deretic et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In general, it is well accepted that NF-κB activation is one of the principal pathways that induce expression of inflammatory molecules in microglia (Wang et al, 2012, Park et al, 2013). Interestingly, increasing evidence suggests the NF-κB pathway as a possible mechanism in which inhibition of autophagy results in attenuation of inflammatory responses (Jiang et al, 2012, Deretic et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several teams of scientists reported its potential physiological basis, by showing that hot-cold medicinal plants may influence differently various parameters: the capillary red blood cell velocity in nail fold microcirculation, pulse characteristics on sphygmogram, hormonal concentrations (serum thyroxin, triiodothyronine, corticosterone, and urine vanillylmandelic acid), metabolic parameters (serum glucose, triglycerides), body weight, enzymatic activities (liver succinate dehydrogenase, liver Na + -K + -ATPase), muscle glycogen, and so on. [334, 339342]. …”
Section: Energetic Nature (Virya) Mediated By Trpsmentioning
confidence: 99%
“…It is common to use Traditional Chinese Medicine and to add specific ingredients including mushrooms, cumquat peel, and lily bulbs to cure specific health conditions and/or restore balance to the body. [10][11][12][13] In the management of FD, it appears that clinicians in the West and Asia routinely dispense lifestyle and dietary advice, probably in response to the patient's association between food bs_bs_banner and their FD symptoms. 14,15 A study by Miura and colleagues, which surveyed the practices of clinicians involved in the treatment of FD in the Asia-Pacific region, found that between 79% and 95% dispensed lifestyle or dietary advice in the treatment of FD and IBS.…”
Section: Dietary Factors Implicated In the Genesis Of Functional Dyspmentioning
confidence: 99%
“…Cultural beliefs related to healing-provoking or illness-provoking qualities of food are manifest in the pervasive concepts of the "cold" and "heaty" essence of food. [10][11][12][13] Frequently, East and Southeast Asians will attempt to restore balance in their health by brewing tonics and soups including items such as dried ginseng, lily bulbs, and black fungus. Patients may delay their presentation to a clinician (frequently referred to as a Western Medicine Practitioner as opposed to a Chinese Medicine Practitioner) in an attempt to selfheal.…”
Section: Functional Dyspepsia In East and Southeast Asiamentioning
confidence: 99%
See 1 more Smart Citation